The effect of debt on corporate profitability: Evidence from French service sector - Mazen Kebewar; Syed Muhammad Noaman Ahmed Shah (Laboratoire d'Economie d'Orléans, 2013)
Current study aims to provide new empirical evidence on the impact of debt on corporate profitability. This impact can be explained by three essential theories: signaling theory, tax theory and the agency cost theory. Using panel data sample of 2240 French non listed companies of service sector during 1999-2006. By utilizing generalized method of moments (GMM) econometric technique on three measures of profitability ratio (PROF1, PROF2 and ROA), we show that debt ratio has no effect on corporate profitability, regardless of the size of company (VSEs, SMEs or LEs). – – L'étude actuelle a pour but de fournir une nouvelle évidence empirique sur l'impact de dette sur la profitabilité d'entreprise. Cet impact peut être expliqué par trois théories essentielles: la théorie du signal, l'influence de la fiscalité et la théorie de l'agence. En utilisant un échantillon d'un panel de 2240 entreprises Françaises non cotées du secteur des services au cours de la période 1999-2006. En utilisant la méthode des moments généralisée (GMM) sur trois mesures de ratio de rentabilité (PROF1, PROF2 et ROA), nous montrons que le ratio de la dette n'a aucun effet sur la profitabilité des entreprises, quelle que soit la taille de l'entreprise (TPE, PME ou ETI).
Keywords: C33; G32; L25; 330; Debt; GMM; Panel data; Profitability